0230 Vaping and Sleep as Predictors of Adolescent Suicidality. (25th May 2022) - Welty, Cody; Nair, Uma; Gerald, Lynn; Skobic, Iva; Morales, Mario; Haynes, Patricia
Abstract: Introduction: Suicide is a leading cause of death for adolescents aged 14-18. Because of the challenges of suicide prevention interventions (e.g., cost or effectiveness), it is critical to examine potential, modifiable risk factors related to adolescent suicide. This study examined self-reported suicidality, vaping, and sleep quantity among high school students in the U.S. We investigated sleep quantity as a moderator of vaping and multiple aspects of suicidality (thoughts, plans, and attempts). This study is, to our knowledge, the first to examine the effects of both vaping and sleep on suicide outcomes. Methods: Authors utilized responses from adolescents with complete data on the primary outcome of a suicide attempt in the past year in the 2019 Youth Risk Behaviors Survey (n=10, 520). Logistic regression was utilized to estimate the main effects of vaping in the past 30 days, sleep hours on school nights, and the interaction of vaping and sleep on suicide attempts (primary outcome), suicidal thoughts (secondary outcome), and suicide plans (secondary outcome). Results: Students who vaped in the past month had 2.78 (95% CI = [2.171-3.549]) times the odds of a suicide attempt in the last year compared to students who did not vape. Students who slept less than seven hours had 1.93 (95% CI = [1.583-2.352]) times the odds of a suicide attempt in the last year compared to students who slept seven or more hours. Sleep quantity moderated the relationship between vaping and suicidal thoughts in the past year but did not moderate the relationship between vaping and a suicide plan or suicide attempts. Specifically, vaping had a reduced effect on suicidal thoughts among students who slept under seven hours. Conclusion: Adolescents who vaped in the past month or who reported less than 7 hours of sleep on school nights had significantly higher odds of reporting a suicide attempt in the past year. Students who vape or report low sleep quantity would be ideal participants in suicide prevention interventions as they may be at higher risk for suicidality. Organizations implementing sleep or vaping interventions should incorporate information regarding the higher odds of suicide among students with low sleep quantity or vaping habits. Support (If Any):